Paternal age and the risk of low birth weight and preterm delivery: a Finnish register-based study. Issue 12 (12th August 2018) - Goisis, Alice; Remes, Hanna; Barclay, Kieron; Martikainen, Pekka; Myrskylä, Mikko
Abstract : Background: Based on existing studies, there is no conclusive evidence as to whether and why paternal age matters for birth outcomes. Methods: We used Finnish population registers on 106 652 children born 1987–2000. We first document the unadjusted association between paternal age and the risk of low birth weight (LBW; <2500 g) and preterm birth (<37 weeks' gestation). Second, we investigate whether the unadjusted association is attenuated on adjustment for child's, maternal and parental socioeconomic characteristics. Third, by adopting a within-family design which involves comparing children born to the same father at different ages, we additionally adjust for unobserved parental characteristics shared between siblings. Results: The unadjusted results show that being born to a father aged 40+, as opposed to a father aged 30–34, is associated with an increased risk of LBW of 0.96% (95% CI 0.5% to 1.3%) and to a younger father (<25) with a 1% (95% CI 0.6% to 1.3%) increased risk. The increased risk at younger paternal ages is halved on adjustment for the child's characteristics and fully attenuated on adjustment for child/parental characteristics. The increased risk at paternal ages 40+ is partially attenuated on adjustment for maternal characteristics (β=0.62%; 95% CI 0.13% to 1.1%). Adjustment for unobserved parental characteristics shared by siblings further attenuates the 40+ coefficient (β=0.4%; 95% CI −0.5% to −1.2%). Results for preterm delivery are similar. Conclusions: The results underscore the importance of considering paternal age as a potential risk factor for adverse birth outcomes and of expanding research on its role and the mechanisms linking it to birth outcomes.